2010
DOI: 10.1007/s00018-010-0527-z
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of phosphate as a specific signaling molecule in bone and other cell types in mammals

Abstract: Although considerable advances in our understanding of the mechanisms of phosphate homeostasis and skeleton mineralization have recently been made, little is known about the initial events involving the detection of changes in the phosphate serum concentrations and the subsequent downstream regulation cascade. Recent data has strengthened a long-established hypothesis that a phosphate-sensing mechanism may be present in various organs. Such a phosphate sensor would detect changes in serum or local phosphate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
114
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 181 publications
(184 reference statements)
2
114
0
1
Order By: Relevance
“…Because calcium and phosphate are key regulators of PTH, it is likely that calcium and phosphate may influence the IGF-1 system directly or indirectly through the PTH pathway. Thus, phosphate and calcium modulate the osteoblastic proliferation through IGF-1 in in vivo studies (29)(30)(31). The bone-forming effects of PTH require involvement of IGF-1, suggesting that IGF-1 plays a role as a potential mediator of the anabolic action of PTH (32).…”
Section: Discussionmentioning
confidence: 99%
“…Because calcium and phosphate are key regulators of PTH, it is likely that calcium and phosphate may influence the IGF-1 system directly or indirectly through the PTH pathway. Thus, phosphate and calcium modulate the osteoblastic proliferation through IGF-1 in in vivo studies (29)(30)(31). The bone-forming effects of PTH require involvement of IGF-1, suggesting that IGF-1 plays a role as a potential mediator of the anabolic action of PTH (32).…”
Section: Discussionmentioning
confidence: 99%
“…Data on the effect of changes in phosphate intake on FGF23 concentrations are inconsistent, with different responses observed with short-term or long-term alterations in phosphate intake (16)(17)(18)(19)(20). It has also been shown that early and rapid changes in renal phosphate excretion occur following a high-phosphorus meal, independent of FGF23, PTH, secreted frizzledrelated protein (sFRP4), or 1,25(OH) 2 D, suggesting the presence of an intestinal 'phosphate sensor', although its exact biochemical nature is not known (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the widespread structural and metabolic functions of Pi, it has become increasingly apparent during the past 15 years that extracellular Pi can act as a signaling molecule directly altering gene expression and cell phenotype (6)(7)(8)(9). The abundance of Pi in the skeleton has led to early studies describing the effects of extracellular Pi in this organ.…”
mentioning
confidence: 99%
“…The ability of organisms to detect changes in extracellular levels of other metabolites (such as Ca 2+ , glucose or amino-acids) has already been described (31)(32)(33), and emerging evidence suggests that similar events are at work to mediate the cellular effects of Pi (8,(34)(35)(36). Although the identity of the molecules involved in these mechanisms is still unknown in mammals, Pi sensing machineries have been characterized in prokaryotic and eukaryotic unicellular organisms (37).…”
mentioning
confidence: 99%